2014
DOI: 10.1590/rou.2014.035
|View full text |Cite
|
Sign up to set email alerts
|

Failure of dental implants in cemento-osseous dysplasia: a critical analysis of a case

Abstract: ResumoIntrodução: Implantes dentários têm sido rotineiramente utilizados como excelente alternativa para a reabilitação oral. Pacientes com doenças ósseas displásicas representam um desafio especial para a reabilitação oral com implantes dentários. No entanto, a instalação de implantes em pacientes com displasia cemento-óssea (DCO) tem sido relatada com aparente sucesso. Objetivo: Neste artigo, apresentamos um caso de um paciente com DCO florida em que um implante dentário fora instalado em paciente com lesões… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 9 publications
(17 reference statements)
1
12
0
Order By: Relevance
“…This tissue can compromise post -surgical repair, directly affecting osseointegration and leading to a greater risk of osteomyelitis. 10 However, other authors found success in implant placement in a patient with FLCOD in regions where the fibro-osseous lesion was absent. 12 In the region where the lesions were present, the authors indicated rehabilitation with a fixed prosthesis, 12 corroborating the procedure adopted in the present study.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…This tissue can compromise post -surgical repair, directly affecting osseointegration and leading to a greater risk of osteomyelitis. 10 However, other authors found success in implant placement in a patient with FLCOD in regions where the fibro-osseous lesion was absent. 12 In the region where the lesions were present, the authors indicated rehabilitation with a fixed prosthesis, 12 corroborating the procedure adopted in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…Due to the COD's avascular characteristics, surgical procedures such as biopsy, extraction, and dental implants should be avoided. 10 COD, especially in the mixed and sclerotic phases, shows a small amount of vascu- larized connective tissue and a large volume of avascular or dense hypovascular osteo-cementoid structures. This tissue can compromise post -surgical repair, directly affecting osseointegration and leading to a greater risk of osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In edentulous patients, while the normal alveolar bone undergoes atrophy the sclerotic masses remain, and local trauma of the tissue-borne dentures can lead to secondary infections of FOD lesions. Additionally, due to the compromised vascularization and plasticity of the cancellous bone, implants osseointegration might be impaired (Sadda & Phelan;Oliveira et al, 2014). Orthodontic treatment may also impair in complications and should be carried with special attention with oral hygiene (Minhas et al, 2008).…”
Section: Discussionmentioning
confidence: 99%